Do the frequency of aortic dissection surgery and 30-day survival depend on the day of the week, climate parameters, or moon phase? - Böning, Andreas; Brühl, Marc; Büsch, Christopher; Luther, Niklas; Xoplaki, Elena; Arif, Rawa; Noack, Thilo; Pöling, Jochen; Czerny, Martin; Brickwedel, Jens; Peterss, Sven; Holubec, Tomas; et al. (The thoracic and cardiovascular surgeon, 2025)
The German Registry of Aortic Dissections Type A (GERAADA) is a large European registry documenting patients with type A aortic dissection who have undergone surgical repair. This analysis investigated a potential association between the incidence of type A dissections (AADA) and lunar cycles, day of the week, or weather conditions. Data from 2,388 patients were analyzed for two endpoints: incidence of AADA surgery per day (analyzed using a Poisson regression to account for overdispersed data) and early mortality after surgery (analyzed using a logistic mixed regression to account for center heterogeneity). In both models, the influence of weather conditions (season, temperature, temperature difference, radiation, and synoptic conditions), moon phase, and weekday of operation was examined. The occurrence of AADA surgery was similar between weekdays (Monday to Friday), but less frequent on weekends. The 30-day mortality odds ratio was higher for surgeries performed on weekends than on weekdays. Operations were more frequent in winter than in other seasons. The occurrence of surgery or early mortality after surgery was not associated with synoptic weather conditions. Mean daily temperature and global radiation were not found to be different between survivors and patients with early deaths. No significant association was found between the moon phase and the occurrence or the outcome of surgery. The occurrence of AADA surgery was higher during winter, with colder mean temperatures, and lower on weekends than on weekdays. Mortality after surgery on weekends was higher than after surgery on weekdays.
Gesehen am 07.10.2025